2014
DOI: 10.4238/2014.march.12.5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and immune response analysis of putative variable lipoproteins from Mycoplasma mycoides subsp capri

Abstract: ABSTRACT. Mycoplasma mycoides subsp capri is the cause of goat "MAKePS" (Mastitis, Arthritis, Keratoconjunctivitis, Pneumonia, Septicemia) syndrome. We identified three genes (GL_ 000459; 000461; 000462) as variable lipoprotein genes in the M. mycoides subsp capri str. PG3 genome by genomic information and comparative genomic analyses. To study the role of variable lipoproteins in M. mycoides subsp capri pathogenesis and evaluate the immunogenic and protective potentials of those proteins, we constructed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Mmc PG3 strain, Mo NM151 strain, Mo NM130 strain, Mo NM85 strain and Mo NM811 strain used were isolated from Huhhot in China. They were recovered and cultured in a modified Hayflick's broth (1.0 g/L glucose, 21.0 g/L PPLO, 0.4 g/L sodium pyruvate, 10 mL of 25% (w/v) yeast extract, 200 mL donor equine serum (HyClone, USA), 10 mL 10,000 IU/mL penicillin-G, 2.5 mL of 0.4% (w/v) phenol red, and 20 mM HEPES at pH 7.6-7.8, adjusted with 0.1 M sodium hydroxide at 37°C, in a 5% CO 2 atmosphere [7]. Solid medium was prepared by adding 1% (w/v) agar to the modified Hayflick's broth.…”
Section: Strain and Culturementioning
confidence: 99%
“…Mmc PG3 strain, Mo NM151 strain, Mo NM130 strain, Mo NM85 strain and Mo NM811 strain used were isolated from Huhhot in China. They were recovered and cultured in a modified Hayflick's broth (1.0 g/L glucose, 21.0 g/L PPLO, 0.4 g/L sodium pyruvate, 10 mL of 25% (w/v) yeast extract, 200 mL donor equine serum (HyClone, USA), 10 mL 10,000 IU/mL penicillin-G, 2.5 mL of 0.4% (w/v) phenol red, and 20 mM HEPES at pH 7.6-7.8, adjusted with 0.1 M sodium hydroxide at 37°C, in a 5% CO 2 atmosphere [7]. Solid medium was prepared by adding 1% (w/v) agar to the modified Hayflick's broth.…”
Section: Strain and Culturementioning
confidence: 99%
“…Another study revealed that the conserved regions in variable Mycoplasma mycoides subsp. caprii lipoproteins stimulate the immune response and may act as immunogenic and protective antigens [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mmc can cause “MAKePS” (Mastitis, Arthritis, Keratoconjunctivitis, Pneumonia, Septicemia) syndrome in ruminants [ 8 ]. In order to better distinguish and prevent CCPP caused by Mccp and reduce the loss of the goat industry, Thiaucourt et al defined other respiratory mycoplasma diseases in small ruminants with the same symptoms as “MAKePS” syndrome.…”
Section: Introductionmentioning
confidence: 99%